(untitled) (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
P2Y receptors (nomenclature as agreed by the NC-IUPHAR Subcommittee on P2Y Receptors [3, 5]) are activated by the endogenous ligands ATP, ADP, uridine triphosphate, uridine diphosphate and UDP-glucose. The relationship of many of the cloned receptors to endogenously expressed receptors is not yet established and so it might be appropriate to use wording such as ’uridine triphosphate-preferring (or ATP-, etc.) P2Y receptor’ or ’P2Y1-like’, etc., until further, as yet undefined, corroborative criteria can be applied [46, 109, 187, 375, 388]. Clinically used drugs acting on these receptors include the dinucleoside polyphosphate diquafosol, agonist of the P2Y2 receptor subtype, approved in Japan for the management of dry eye disease [236], and the P2Y12 receptor antagonists prasugrel, ticagrelor and cangrelor, all approved as antiplatelet drugs [52, 316].